HISTOMORPHOLOGICAL CHANGES IN OVARY OF GOAT DURING VARIOUS STAGES OF FOLLICULOGENESIS - POYAM, M R; TIWARl, R P; INGOLE, S P (The Indian Journal of Animal Reproduction, 2011)
The present investigation was carried out to study the histomorphological changes in ovaries of adult nondescript goat (Capra hircus) during various stages offolliculogenesis in the month of August to November 2005. The reproductive organs free from gross pathological lesions with follicles on ovaries of 30 adult non-descript, non pregnant female goats were collected from the Government Slaughter House, Supela, Bhilai (C.G). The ovaries were kept intact with individual identity tag and were brought to the laboratory in normal saline solution at 37°C temperature in Thermos flask quickly. On arrival at the laboratory ovaries were trimmed of the extraneous tissue, washed free of blood and detritus using normal saline solution. The ovaries were classified on the basis of size of the largest follicle on surface of one of the ovaries as in group A up to 4 mm, group B 4-6 mm and group C more than 6 mm, each group consisted of 10 pairs of ovaries. Histomorphologically the ovary was covered by germinal epithelium which decreased in height from 8.34 ± 0.99 μmin group A to 5.22 ± 1.033 μmin group C . The shape changed from cuboid al to squamous type. The range of diameter of the follicles was 96.00 - 691 .09 μm, 720.00 - 1440.00 μm and 2400.00 - 4032.00 μm in group A, Band C respectively. The membrana granulosa and liquor folliculi gave intense positive response to PAS-Alcian blue.